2022
DOI: 10.1039/d2sm00499b
|View full text |Cite
|
Sign up to set email alerts
|

Bond strength regime dictates stress relaxation behavior

Abstract: This work utilizes in situ crosslinked dynamic networks to show differences in stress-relaxation behavior depending on the bond strength of the metal–ligand crosslinker used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Examples include double networks, , host–guest interactions, , hydrogen bonding, and metal–ligand interactions, , with metal–ligand systems having the added advantage of tunability via the strength and nature of the metal–ligand bond. This feature allows network stiffness and relaxation properties to be controlled through careful selection of metal–ligand dissociation times. , …”
Section: Introductionmentioning
confidence: 99%
“…Examples include double networks, , host–guest interactions, , hydrogen bonding, and metal–ligand interactions, , with metal–ligand systems having the added advantage of tunability via the strength and nature of the metal–ligand bond. This feature allows network stiffness and relaxation properties to be controlled through careful selection of metal–ligand dissociation times. , …”
Section: Introductionmentioning
confidence: 99%
“…They are known to affect the bandgap, leading to structural instability, an increase in defect density, reduced carrier mobility, increased ionic mobility, higher risk of cracking or mechanical failure, and lower cell efficiency. As shown in Figure a, an applied tensile stress can cause the perovskite film to break down into a yellow PbI 2 phase and create a path for rapid ion migration, which might relieve some of the thermally induced stress. Stress relaxation is a common effect seen in different classes of materials and is ascribed to the breaking of bonds in metals or the movement of polymer chains in elastic fibers . Previous research on stress in perovskite solar cells has shown that tension leads to an increase in ion migration and accelerates breakdown of methylammonium lead iodide to lead iodide .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Herein, the chemical bonds holding the network together are no longer static and permanent, but dynamic, where they break and reform at appropriate processing conditions. The use of non-covalent bonds, 5,6 dynamic covalent bonds, [7][8][9] and combinations thereof 10,11 has been explored in detail to achieve such dynamic properties. These investigations not only elucidated the different mechanisms by which bond exchange reactions can occur, 12 either associative or dissociative, but also highlighted the importance of the nature of the chemical bond, 5,13 the network topology, 14,15 and the time scales at which relaxation processes occur.…”
Section: Introductionmentioning
confidence: 99%
“…The use of non-covalent bonds, 5,6 dynamic covalent bonds, [7][8][9] and combinations thereof 10,11 has been explored in detail to achieve such dynamic properties. These investigations not only elucidated the different mechanisms by which bond exchange reactions can occur, 12 either associative or dissociative, but also highlighted the importance of the nature of the chemical bond, 5,13 the network topology, 14,15 and the time scales at which relaxation processes occur. 1,3,16,17 Non-covalent bonds such as hydrogen bonds, for example, show fast relaxation processes at higher temperatures, whereas those of their dynamic covalent counterparts are much slower.…”
Section: Introductionmentioning
confidence: 99%